2022
DOI: 10.1093/pnasnexus/pgac182
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Wolffian duct mesenchyme to the formation of the female reproductive tract

Abstract: The female reproductive tract develops from its embryonic precursor, the Müllerian duct. In close proximity to the Müllerian duct lies the precursor for the male reproductive tract, the Wolffian duct, which is eliminated in the female embryo during sexual differentiation. We discovered that a component of the Wolffian duct, its mesenchyme, is not eliminated after sexual differentiation. Instead, the Wolffian duct mesenchyme underwent changes in transcriptome and chromatin accessibility from male tract to femal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 94 publications
2
7
0
Order By: Relevance
“…It has been reported that Igf1 is enriched in the cranial MD (future oviduct). 20 Our Tcf21 RNAscope staining confirmed the enriched expression of Tcf21 in the mesothelial layer of the uterus but not in the oviduct (Figure 2C). These results validated F I G U R E 5 Gene expression comparison between oviductal and uterine pericytes.…”
Section: Pericytes and Mesothelial Cellssupporting
confidence: 53%
See 1 more Smart Citation
“…It has been reported that Igf1 is enriched in the cranial MD (future oviduct). 20 Our Tcf21 RNAscope staining confirmed the enriched expression of Tcf21 in the mesothelial layer of the uterus but not in the oviduct (Figure 2C). These results validated F I G U R E 5 Gene expression comparison between oviductal and uterine pericytes.…”
Section: Pericytes and Mesothelial Cellssupporting
confidence: 53%
“…The manufacturer's protocol was followed as previously described. 20 Briefly, paraffin sections were treated with antigen retrieval buffer and proteinase. Sections were hybridized with the following individual probes (Angptl7, Cat #: 552821; Wfdc1, Cat #: 471331; Tcf21, Cat #: 508661; Nefm, Cat #: 315611; Gsap, Cat #: 318661) and subjected to rinsing and signaling detection at designated temperatures.…”
Section: Rna-scopementioning
confidence: 99%
“…6B ). It has been reported that Igf1 is enriched in the cranial MD (future oviduct) (56). Our Tcf21 RNAscope staining confirmed the enriched expression of Tcf21 in the mesothelial layer of the uterus but not in the oviduct ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been noticed that the neural crest cells invade into the mesometrial pole of the Müllerian duct (79). Also, during sexual differentiation, Wolffian ducts degenerate in females however the mesenchyme surrounding Wolffian ducts is maintained and contributes to mesenchymal cells at the mesometrial side of the uterus (56). These observations suggest that Nefm+ mesenchymal subpopulation might derive from neural crest cells and/or Wolffian duct mesenchyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation